Evaluation of filter and extraction kits for eDNA-based quantification of Northern pike density - Svensson, Ofir (2021)
Multi-mesh gillnets are the most common gear in Swedish fish monitoring programs. The method works for many fish species but has limitations. The popular game fish Northern pike (Esox lucius) represents one of the species where the gillnet strategy has difficulties to reliably estimate density and to accurately provide data for reliable status assessments. Environmental DNA (eDNA) could be a useful complementary tool to standard surveys if it can provide reliable estimates of pike density.